Analisis Penentuan Strategi Pemasaran Online Berbasis Media Digital di Toko Hyunahijab Menggunakan Metode SWOT - Ai Nurul Kausar; Fitri, Sulidar; Taufiq, Muhammad (Program Studi Pendidikan Teknologi Informasi, 2025)
The rapid growth of the business world is marked by an increasing number of new entrepreneurs and increasingly intense competition. Marketing strategy is essentially a comprehensive, integrated, and unified plan in the field of marketing that provides guidance on activities to be carried out to achieve the marketing goals of a company. This study aims to identify the online marketing strategies used by Hyunahijab Store. This research employs the SWOT method to analyze online marketing strategies through strengths, weaknesses, opportunities, and threats, resulting in four development strategies: (1) aggressive strategy, (2) diversification strategy, (3) turn-around strategy, and (4) defensive strategy. The results of the analysis will serve as recommendations for marketing strategies used by Hyunahijab Store in Tasikmalaya.